TRAVEL TO COUNTRY IATROGENIC (Message 2) - L. I. Dvoretsky (SINAPS LLC, 2017)
The problem of iatrogenesis inevitably dictates the need for not only an exhaustive definition (which in principle is impossible), but also classification with a division into different species. The article deals with the main types of iatrogenia, the classification of iatrogenic proposed by I.A. Kassirsky, E.M. Tareev, S.Ya. Doletsky, A.V. Smolyannikov, V.V. Nekatchalov, and others, which are based on various principles and approaches. Given the expanded interpretation of iatrogenic and the need for a multidisciplinary approach to this problem among iatrogenic events, it is suggested to distinguish the following types of iatrogenic: psychogenic, hospital, therapeutic and preventive, iatrogenic diagnostic studies. Particular attention is paid in the article to psychogenic iatrogenia, which often arises in the process of communication between a doctor and patients. They consider not only iatrogenia, «having a starting point for the behavior of a doctor», but also iatrogenia, caused by certain traits of the patient's character (insecurity, propensity to anxiety fears, increased attention to the slightest changes in health, emotional vulnerability, etc.), predetermining inadequate reactions to any Medical information. Of no small importance in the development of psychogenic iatrogenia is the quality of the medical documentation issued by the doctor to the patient (extracts from the case histories, advisory opinions, descriptions of research results, recommendations, etc.). In this case, it is necessary to avoid formulations that, without proper explanation, may be inadequately perceived by the patient and alert him or her. To the sources of psychogenic iatrogenic, some authors also refer to improperly conducted medical education, the publication of contentious, nonscientific results that do not meet the requirements of evidence-based medicine, although the doctor may not directly participate in this. The author of the article encourages colleagues to pay more attention to the process of communication with the patient, the preparation of documentation in the process of patient management, to remember that psychogenic iatrogenia can have negative consequences for the patient, and can be a source of violation of the relationship between the doctor and the patient.